Study of seed-germination and etiolation of seedlings in Emilia-sonchifolia (l) dc and Emilia-fosgerbii nicolson (Asteraceae) - Correa, A. P.; Takaki, M. (Inst Tecnologia Parana, 1995)
The germination of seeds of Emilia sonchifolia (2n) and E. fosgerbii (4n) was analysed and our results indicate that the former present light insensitive seeds and the latter germinated only under continuous white light. The germination of seeds under shade light presented no differences between both species, However under continuous white light, which maintain 70% of Pfr, the velocity of germination was greater in Emilia sonchifolia when compared to Emilia fosbergii, indicating that the threshold of 4n seeds were greater than 2n seeds. The analysis of the fluence response curves for etiolating process indicated that the process presented no differences between both species. The same was observed for the effect of the shade light in the etiolating process.
Keywords: LIGHT; SEED GERMINATION; EMILIA; SEEDLING; PHYTOCHROME; PLOIDY